MODELING PRODUCTION PROCESSES USING SIMUL8 SOFTWARE IN THE CONTEXT OF TEACHING TECHNICAL SUBJECTS - SEDLÁČEK, Michal (Trends in education, 2020)
The paper deals with the possibility of using modeling and simulation tools in the teaching process. Emphasis is placed on their application in teaching technical subjects in the form of a demonstration tool. Simul8 program was chosen as a software tool, which is primarily used for modeling logistic processes based on discrete simulation and enables creation of visual models of production, distribution, economic and other processes. The paper is focused on the steps of the process of creating simulation models of production processes and the possibilities of their use in the educational process focused on the development of technical thinking.
Keywords: Simulation Model; Simul8 Software; Demonstration Tool; Technical Education; Critical Thinking.